2018
DOI: 10.1186/s13058-018-1035-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal breast cancer risk in relation to birthweight and gestation of her offspring

Abstract: BackgroundParity and age at first pregnancy are well-established risk factors for breast cancer, but the effects of other characteristics of pregnancies are uncertain and the literature is inconsistent.MethodsIn a cohort of 83,451 parous women from the general population of the UK, which collected detailed information on each pregnancy and a wide range of potential confounders, we investigated the associations of length of gestation and birthweight of offspring in a woman’s pregnancies with her breast cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…The present systematic review and meta-analysis suggested an increase in the BC risk (RR = 1.03) in women with a PB 26-31 gestational weeks compared to 40-41 gestational weeks. Similar to our study, Swerdlow et al [23] have shown in their study that the risk in women with gestational age of 26-31 weeks was 2.4 times compared to 40-41 weeks. Previous studies as well as the results of this study showed that early delivery may increase the risk of BC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present systematic review and meta-analysis suggested an increase in the BC risk (RR = 1.03) in women with a PB 26-31 gestational weeks compared to 40-41 gestational weeks. Similar to our study, Swerdlow et al [23] have shown in their study that the risk in women with gestational age of 26-31 weeks was 2.4 times compared to 40-41 weeks. Previous studies as well as the results of this study showed that early delivery may increase the risk of BC.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies as well as the results of this study showed that early delivery may increase the risk of BC. Swerdlow et al [23] have suggested that hormonal stimulation and breast proliferation at the beginning of pregnancy and the lack of enough opportunity for differentiation that occurs at the end of pregnancy are the cause of this relationship. Mammary cells in human and animals differentiate in the third trimester [28][29][30] and therefore a full term pregnancy is considered as a protective factor for BC [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with preterm delivery in anamnesis have also been shown to have an increased risk of subsequent ophthalmic complications, such as diabetic retinopathy and glaucoma [ 24 ], chronic kidney disease, end-stage kidney disease [ 25 ], and breast cancer [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the association between birthweight and breast cancer has been attracted much research interest. Although a positive correlation between women's birthweight and breast cancer risk was discovered in some studies (11,12,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), some others failed to replicate such connection or even detected inconsistent correlations in effect direction (13,15,21,22,(33)(34)(35)(36)(37)(38)(39)(40)(41). These inconsistent ndings may be partly due to potential confounding in uences commonly arisen in observational studies, making it di cult to draw a de nitive conclusion on the causal association between birthweight and breast cancer.…”
Section: Introductionmentioning
confidence: 99%